Influence of Varying Temperature and Concentration on Magnetohydrodynamics Peristaltic Transport for Jeffrey Fluid with a Nanoparticles Phenomenon through a Rectangular Porous Duct - Dheia Gaze Salih (مجلة بغداد للعلوم)
A mathematical model constructed to study the combined effects of the concentration and the thermodiffusion on the nanoparticles of a Jeffrey fluid with a magnetic field effect the process of containing waves in a three-dimensional rectangular porous medium canal. Using the HPM to solve the nonlinear and coupled partial differential equations. Numerical results were obtained for temperature distribution, nanoparticles concentration, velocity, pressure rise, pressure gradient, friction force and stream function. Through the graphs, it was found that the velocity of fluid rises with the increase of a mean rate of volume flow and a magnetic parameter, while the velocity goes down with the increasing a Darcy number and lateral walls. Also, the velocity behaves strangely under the influence of the Brownian motion parameter and local nanoparticle Grashof number effect.